Investigation of Vancomycin Usage in Adult Patients at Quang Ninh Hospital - Ba Hai, Le; Thi Lam, Dam; Thi Linh, Phan; Chi Kien, Phung; Thi Hai Ninh, Pham; Van To, Dong; Thanh Hai, Nguyen (VNU Journal of Science: Medical and Pharmaceutical Sciences; Vol 41 No 3, 2025)
Objectives: To describe the usage of vancomycin in adult patients in Quang Ninh Provincial General Hospital. Subject and method: Retrospective descriptive study based on data obtained from medical records of adult inpatients (≥ 18 years old) in Quang Ninh Provincial General Hospital during the period from 01/06/2023 to 31/08/2023 treated with intravenous vancomycin for at least 24 hours. Results: The median age of the 131 patients was 62 years, with men accounting for 71.8%. Patients discharged from the hospital with recovery/improvement accounted for 82.4%. Vancomycin was prescribed empirically in 97% of patients. The rate of patients undergoing microbiological culture was 71.8%. Of the 52 specimens with positive results, Staphylococcus aureus accounted for 26.9%, with Methicillin-resistant Staphylococcus aureus (MRSA) constituting 64.2%. A loading dose regimen was applied in 5.3% of patients. The common maintenance doses were 1g/24h (59.2%). The rate of patients experiencing nephrotoxicity was 3.05%. Conclusion: The study noted that the proportion of patients prescribed a loading dose was very low, and the majority of patients were not prescribed a maintenance dose appropriately for their kidney function. Therefore, Quang Ninh Provincial General Hospital needs to promote the role of clinical pharmacists in the management of appropriate antibiotic use, develop procedures, and monitor vancomycin blood levels to guide individualized treatment.